Assessing the readiness of Filipino MRA-supported professions to participate in the mobility of skilled labor in the ASEAN region: Lessons for APEC economies - John Paolo R. Rivera; Cynthia P. Cudia; Tereso S. Tullao (Philippine Institute for Development Studies (PIDS), 2019)
As a single market and production base, the ASEAN Economic Community (AEC) enabled ASEAN Member States (AMS) to take advantage of the free flow of goods, services, funds, and labor. The free movement of labor, particularly skilled, to economies with lucrative opportunities allows them to realize higher returns on their investments in human capital. Such movement is facilitated by mutual recognition arrangements (MRAs) where AMS agreed on recognition mechanisms (i.e., equivalence of registration, licensing requirements, and reciprocity requirements) that facilitated mobility of skilled professionals within the region, strengthened trade in services, and further deepen the AEC. As such, we conduct an extensive analysis of the contributions of MRAs in enhancing the quality of professional services through human resource development (HRD), specifically in the Philippines. In addressing our inquiry whether Filipino professions with MRA support (i.e., accountancy services, medical practitioners, architectural services, engineering services, and tourism professionals) are ready to participate in the mobility of skilled professionals in the AEC, we are able to prepare Filipino professionals, in terms of education, continuing professional education, licensure examinations, experience and others, to be comparable with the existing MRAs for each profession. Through document review and analysis as well as a validation workshop with experts for each profession, we would be able to pinpoint specific avenues of HRD that will increase competitiveness of Filipino professionals in the region. Results will provide a lens on analyzing the mobility of skilled workers through MRAs, which are meant to enable policymakers in making Filipino professionals as well as the entire ASEAN region highly competitive. This will also provide lessons for other economies, particularly APEC economies, on how HRD can enhance labor competitiveness.
Keywords: 330; ASEAN economic community; human resource development; movement of natural persons; mutual recognition arrangements